Hypertension and its correlates among in‑school adolescents in Ekiti State, South‑west, Nigeria - Emmanuel, Eyitayo Ebenezer; Dada, Samuel Ayokunle; Amu, Eyitope Oluseyi; Aduayi, Victor Adovi; Atoyebi, Oladele Ademola; Marcus, Oluwadare; Ibirongbe, Demilade Olusola (Asian Journal of Medical Sciences, 2017)
Background: Hypertension is one of the major risk factors for cardiovascular disease (CVD). Though generally believed to be a disease of the adults, It has been shown to start in early life and tracks through adolescence into adulthood. Aims and Objectives: The objective of this study was to determine the prevalence of hypertension and associated factors among adolescents in Ekiti State. Materials and Methods: The study was a cross sectional survey involving 416 secondary school adolescents aged 10 to 19 years. A ‘two-stage’ sampling technique was used to select the subjects. Facilitated self-administered questionnaire was used for the study. Data was analyzed using SPSS version 20. Level of significance was set at P<0.05. Results: A total of 416 students participated in the study. Prevalence of hypertension was 10.1% with male and female prevalence rates of 5.8% and 14.4% respectively (P=0.004). Hypertension was higher among adolescents with BMI ≥ the 85th percentile for age and sex compared to those with lower BMI (P=0.004). There was a weak positive correlation between BMI and blood pressure in the study (Systolic r=0.33, P=0.001: diastolic r=0.31, P=0.001). Conclusion: The study concluded that hypertension is not a rare phenomenon among adolescents and that female gender and high BMI were the main risk factors for adolescent hypertension in this study. Asian Journal of Medical Sciences Vol.8(4) 2017 1-5